Antibiotic resistance in Escherichia coli isolated from United Kingdom dairy cow faeces - Marsh, Caleb (2025)
Antimicrobials are essential tools in modern human and veterinary medicine, but antimicrobial resistance (AMR) is reducing their effectiveness. The global AMR objective of increased stewardship to achieve sustainable antimicrobial use (AMU) has been a priority for many years, with increased attention after 2015. This approach has significantly reduced AMU overall in some key areas. However, the impact of reduced AMU on the risk of AMR needs to be better understood through surveillance of AMU and AMR. This thesis directly contributes to this global objective, making it a crucial part of the ongoing fight against AMR. Specific challenges in the dairy industry have resulted in significant AMU and AMR data gaps. Is the available data sufficient to understand the current risk of resistance, gauge the success of current approaches and inform future decision-making? This work presents a baseline for the antibiotic susceptibility of bovine faecal Escherichia coli (E. coli) from dairy cows on a single farm in the United Kingdom (UK); it also investigates the impact of chemotherapeutic treatment given to cows and the physiological development of cows. Over three years, 38 convenience faecal samples were collected from different bovines across several developmental stages from a single farm. E. coli was selected as the model organism for faecal bacteria as E. coli are well-characterised commensal bacteria and opportunistic pathogens in humans and bovines. A combined approach of direct culture on selective media and antibiotic susceptibility testing of faecal E. coli (the current gold standard) with next-generation short-read sequencing, shotgun metagenomics, and in silico phenotype prediction was used. The total outputs of this combined approach were the isolation of over 800 bovine faecal E. coli with antibiograms to six classes of antibiotics, the identification of three transmissible MDR phenotypes, 160 bovine faecal E. coli whole genomes, and 20 bovine faecal metagenomes. Resistance to several important antibiotics and the associated antibiotic resistance genes have been identified. The genetic diversity of these E. coli and the diversity of the faecal metagenomes from which they were isolated were also investigated. This thesis demonstrates that chemotherapy increases the proportion of antibiotic resistant E. coli in faeces and that this proportion decreases as time after treatment increases. The antibiotic susceptibility phenotypes of the E. coli from all of the adult animals were similar. However, a higher level of antibiotic resistance was identified in the E. coli sourced from dairy calves. The differences in the faecal metagenomes of these developmental groups provide a possible explanation for these differences in E. coli antibiotic susceptibility. Differences in animal physiology and diet affect the faecal metagenome, affecting the microbiome composition. The findings of this thesis contribute evidence for the data gaps around AMR in the UK dairy industry and inform discussions around antimicrobial stewardship, dairy cow faecal microbiomes, and the need for biosecurity measures focusing on calf health as a priority. In conclusion, this thesis represents a significant investigation of antibiotic resistance in E. coli isolated from UK dairy cow faeces.